2015
DOI: 10.1590/0103-6440201300116
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT Evaluation of Non-instrumented Canal Areas with Different Enlargements Performed by NiTi Systems

Abstract: The aim of this study was to compare the percentage of non-instrumented area of root canals prepared with different enlargements using single-file reciprocating systems (Reciproc and WaveOne) and a conventional multi-file rotary (BioRaCe) system by microcomputed tomographic analysis. Thirty mesial roots of mandibular molars with moderate curvature (10° to 20°) presenting a type II Vertucci canal configuration and similar internal volume were chosen and scanned at an isotropic resolution of 14.16 µm. The sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
91
1
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 26 publications
13
91
1
18
Order By: Relevance
“…, De‐Deus et al . ). Amongst the tested systems, the SAF and Reciproc systems had the lowest percentage of untouched canal area.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…, De‐Deus et al . ). Amongst the tested systems, the SAF and Reciproc systems had the lowest percentage of untouched canal area.…”
Section: Discussionmentioning
confidence: 97%
“…, De‐Deus et al . ) and accumulated hard‐tissue debris in fins, isthmuses and irregularities within the root canal space (Paqué et al . , De‐Deus et al .…”
Section: Introductionmentioning
confidence: 99%
“…In endodontics, image volume resulting from scanning of teeth, before and after cleaning and shaping procedures, can be geometrically co-registered into one coordinate system allowing identification and measurement of several important outcome parameters such as hard-tissue debris packed into root canal complexities (11)(12)(13), changes in canal volume (10), percentage of shaped canal walls (14), transportation degree (15) and spreadability of irrigants (16). Besides, micro-CT has already been successfully used to investigate cracks within tooth structure (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Gergi et al ( 39 , 41 ) compared the root canal anatomy preservation and non-instrumented areas with Reciproc®, Wave One® and TF® size 25 files, finding no significant differences in non-instrumented areas (P>0.05), but better root canal anatomy preservation results with TF® (P<0.05). De-Deus et al ( 42 ) investigated non-instrumented areas for size 25 and 40 Reciproc®, Wave One® and BioRace® files and concluded that there were no significant differences between all any of the systems (P>0.05). Unlike Gergi et al and De-Deus et al, the present study found significant differences in non-instrumented areas in the middle and apical thirds, but Reciproc® was significantly better (P<0.05), probably due to its S cross-section, reciprocating movement and taper.…”
Section: Discussionmentioning
confidence: 99%